Diagnosing awareness in disorders of consciousness with gamma-band auditory responses - Binder, Marek; Papiernik, Julia; Griskova-Bulanova, Inga; Frycz, Sandra; Chojnacki, Bartłomiej; Górska-Klimowska, Urszula (Frontiers in Human Neuroscience, 2024)
The prolonged disorders of consciousness (pDOC) describe a group of neurological conditions characterized by severe impairment of consciousness resulting from the injury of the central nervous system. As the behavioral diagnosis of pDOC remains challenging, the methods based on observing brain activity appear as promising alternatives. One of these methods is electroencephalography, which allows for noninvasive assessment of brain function. In this study, we evaluated evoked auditory responses to the chirp-modulated auditory stimulation as a potential biomarker of awareness in pDOC. Chirp-modulated stimulation is based on the repetitive presentation of auditory stimuli with a changing frequency over time. Two protocols were tested: amplitude-modulated narrow-band chirps (frequency range 25-55 Hz) and click-based wide-band chirps (30-100 Hz). The studied pDOC patient group included 62 patients (19 females and 43 males, mean age 40.72 years) diagnosed with Coma Recovery Scale-Revised. Envelope-following responses to stimulation were examined using the intertrial phase clustering coefficient. For both types of stimulation, the strength of the response in the low-gamma range (around 40 Hz) was related to the diagnosis of pDOC. Patients diagnosed with unresponsive wakefulness syndrome exhibited diminished responses, while more favorable diagnoses, suggesting awareness (minimally conscious state or emergence from the minimally conscious state), showed elevated responses. The variations in the integrity of the auditory pathway and the etiology of brain injury altered the observed response strength. Narrow-band stimulation yielded a more systematic relationship between low-gamma response and pDOC diagnosis. The results suggest the potential role of low gamma-band responses to chirp-modulated stimulation as the supportive diagnostic tool to detect awareness in the pDOC patient group.